A rare case of pediatric cardiomyopathy: Alström syndrome identified by gene panel analysis. Issue 12 (27th October 2020) - Spinelli, Valentina; Girolami, Francesca; Marrone, Chiara; Consigli, Veronica; Iascone, Maria; Passantino, Silvia; Porcedda, Giulio; Calabri, Giovanni Battista; De Simone, Luciano; Olivotto, Iacopo; Santoro, Giuseppe; Favilli, Silvia
Abstract: Genetic investigation of early‐onset Dilatative cardiomyopathy phenotype, including molecular autopsy, is the key to appropriate recognition and management of rare etiologies and atypical presentations and to offer genetic counseling to the family. Abstract : Genetic investigation of early‐onset Dilatative cardiomyopathy phenotype, including molecular autopsy, is the key to appropriate recognition and management of rare etiologies and atypical presentations and to offer genetic counseling to the family.